Hubungan Lingkungan Kerja Dengan Kepuasan Kerja Karyawan - Bidaya, Nurmeseri Cordias Agung; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
This study aims to determine the relationship between the work environment and employee job satisfaction. A good work environment is believed to create a sense of comfort and security for employees, thus impacting their job satisfaction levels. This study used a quantitative approach with a correlational design. Data were obtained by distributing questionnaires to employees in an organization. Data analysis techniques used the Pearson correlation test and simple linear regression. The results of the study indicate that the work environment has a positive and significant relationship with employee job satisfaction. This finding indicates that improving the work environment, both physical and non-physical, can increase employee job satisfaction. This research is expected to provide management with a consideration in managing the work environment effectively.